Pelejas em rede: vamos ver quem pode mais - Amorim, Maria Alice (2012)
The Cordel Literature, also known as string literature , constitutes one of the traditional poetical verses of Northeastern Brazil, characterized by the written production and specific typographic records. The communicational processes occupy, hence, a privileged position. In the last two decades, the cordelists have started performing through poetic contests by means of e-mail or chat communities on social networks, publishing what is called virtual battles , battles based on the cordel s imaginary battles, which can already be seen in titles of the 20th century. Thus, these written contests tradition harks back to the poetic challenges between two improvisers who would perform before an enthralled audience. The contests of cordelists and improvisers safe guard several codes and simultaneously interweave poetical elements which have been updated for centuries. Combining fixed forms, rhythm, themes, verbal duels, be they improvised or not, are recurrent in the poetry of cordelists, guitar players, coquistas, cirandeiros, maracatu masters, carnival ox, caboclinhos, rural carnival parades, samba of the countryside man. Face to face challenges, printed challenges, web-mediated challenges pave the way for the articulation of these expressions into a great poetical, oral text going through a continuous process in updating the virtual matrices. The research corpus harbors battle booklets (virtual and fictional); face-to-face challenges; poetry performing events; recorded virtual battles that took place on the web, cds and dvds by improvisers and cordelists. Participants observation, interviews and qualitative analysis of large texts that have been utilized in virtual contests (mediated by twitter, msn, facebook, orkut, sites, portals, email, and so forth) are in the methodology covering the fictional battles of cordelists and improvisers. Pursuant to the interdisciplinary concepts of communication by Jesús Martín-Barbero; tradition, performance and movement by Paul Zumthor; great oral text and virtual matrices by Jerusa Pires Ferreira; cyber-culture by Francisco Rüdiger, I propose to carry out a comparative study on the production of improvisers and cordelists spanning mainly the decades from 1990/2000. The purpose of the study is to investigate the existence of memories confluence and combination in the articulation of this large communication text in an ever adapting process, and also to speculate to what extent one can define such poetry as a recognizable cultural series